Love and Moral Boundaries of Religion as a Reflection of Cultural Da'wah in the “Haramkah” Song by Melly Goeslaw - Parikesit, Bangun Krismu; Mudzakkir, Fakhruddin; Maskuri, M. Ibnu Naufal (Jurnal Ilmiah Syi'ar, 2025)
In the context of modern society, Islamic da‘wah faces significant challenges in conveying moral and spiritual values in ways that remain relevant amid the dominance of popular culture and entertainment media. Popular music, often perceived as a profane cultural space, is frequently questioned in terms of its capacity to function as an effective and non-dogmatic medium of da‘wah. Against this backdrop, this study aims to analyze the song “Haramkah” by Melly Goeslaw as a reflection of cultural da‘wah that communicates Islamic moral values through popular music. This study employs a qualitative approach using lyrical text analysis, combined with the theoretical framework of Islamic communication and cultural da‘wah. The main focus is on how concepts of love and religious moral boundaries are aesthetically interpreted within the song’s lyrics, as well as how da‘wah messages are presented in a reflective and humanistic manner rather than in a dogmatic form. The findings indicate that “Haramkah” represents the inner struggle of modern individuals between romantic desire and moral consciousness, with the lyrics emphasizing the importance of self-restraint and the surrender of the heart to God. Music functions as a medium of emotional communication that integrates moral messages, affective experiences, and the listener’s religious awareness. The song illustrates a dialectical relationship between religion and popular culture, in which Islamic values are articulated through aesthetic forms that are accessible and relevant to urban life. Implications of this study highlight the potential of cultural da‘wah in fostering moral and spiritual awareness in modern society, while also expanding scholarly understanding of the transformation of Islamic da‘wah in the era of media and popular arts.